How we think about dementia : personhood, rights, ethics, the arts and what they mean for care - Hughes, Julian C. (Jessica Kingsley Publishers, 2014)
Providing a much-needed accessible overview of the complex philosophical and ethical underpinnings of dementia care, this book explores current thinking around the concepts of ageing, personhood, capacity, liberty, best interests and the nature of palliative care, shedding new light on their implications for the caring professions.